The body mass index profiles in chronic pulmonary aspergillosis: trend and variability in post tuberculosis patients - Findra Setianingrum; Anna Rozaliyani (Universitas Muhammadiyah Surabaya, 2024)
Tuberculosis (TB) is the main risk factor for chronic pulmonary aspergillosis, especially in patients with residual cavitary lesions after completion of TB therapy. The body mass index (BMI) is one of the established markers in predicting the mortality of CPA. However, the data regarding BMI profiles of CPA patients in Indonesia is still limited. We evaluated the BMI profiles of CPA patients among post-TB patients. Patients diagnosed as CPA based on clinical, radiology and the Aspergillus IgG test. 50 patients were included with a mean age of 35 years; 13 patients met the criteria of CPA. The overall median of BMI in these patients was 21. The median BMI in the CPA group was 19,3. The lowest (19,8) median BMI value was observed in the positive Aspergillus IgG group (11,5 – 30 mg/L) with a minimum BMI of 14,7 and a maximum BMI of 29,2. The differences in median BMI across CPA and non CPA groups and Aspergillus IgG level were not statistically significant. However, there is a trend that lower BMI were distributed among patients with positive Aspergillus IgG. More than one third of CPA patients in this study were classified as underweight. Future study is necessary to better depict the BMI profiles in larger scale of populations of CPA in Indonesia in order to achieve better diagnosis and management of CPA.